Evaluating accelerometry thresholds for detecting changes in levels of moderate physical activity and resulting major mobility disability - Rejeski, W. Jack; Walkup, Michael P.; Fielding, Roger A.; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; McDermott, Mary McGrae; Miller, Emily Y; Newman, Anne B.; Tudor-Locke, Catrine; Axtell, Robert S.; Miller, Michael E. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2018)
Background: An important decision with accelerometry is the threshold in counts per minute (CPM) used to define moderate to vigorous physical activity (MVPA). We explore the ability of different thresholds to track changes in MVPA due to a physical activity (PA) intervention among older adults with compromised function: 760 CPM, 1,041 CPM, and an individualized threshold. We also evaluate the ability of change in accelerometry and self-reported PA to attenuate treatment effects on major mobility disability (MMD). Methods: Data from a week of hip worn accelerometers and self-reported PA data (30-day recall) were examined from baseline, 6-, 12-, and 24-months of follow-up on 1,528 older adults. Participants were randomized to either PA or Health Education (HE). MMD was objectively defined by loss of ability to walk 400 m during the follow-up. Results: The three thresholds yielded similar and higher levels of MVPA for PA than HE (p ¡ .001), however, this difference was significantly attenuated in participants with lower levels of physical function. Self-reported PA that captured both walking and strength training totally attenuated the intervention effect for MMD, an 18% reduction to a 3% increase. Accelerometer CPMs showed less attenuation of the intervention effect. Conclusions: Accelerometry assessment within the LIFE study was not sensitive to change in level in physical activity for older adults with very low levels of physical function. A combination of self-report and objective measures are recommended for use in physical activity intervention studies of the elderly; limitations of accelerometry deserve closer attention.
Keywords: Accelerometry; Aged; Aged, 80 and over; Female; Geriatric Assessment; Humans; LIFE-study; Male; Mobility Disability; Mobility Limitation; Motor Activity; Older Adults; Thresholds; Walking; accelerometry; aged; clinical trial; controlled study; dept.hms; female; geriatric assessment; human; male; motor activity; multicenter study; peer-reviewed; physiology; procedures; randomized controlled trial; very elderly; walking; walking difficulty